2015
DOI: 10.1115/1.4029085
|View full text |Cite
|
Sign up to set email alerts
|

Transient Couple Stress Fluid Past a Vertical Cylinder With Bejan’s Heat and Mass Flow Visualization for Steady-State

Abstract: In the present study, the transient, free convective, boundary layer flow of a couple stress fluid flowing over a vertical cylinder is investigated, and the heat and mass functions for the final steady-state of the present flow are developed. The solution of the time dependent nonlinear and coupled governing equations is obtained with the aid of an unconditionally stable Crank–Nicolson type of numerical scheme. Numerical results for the time histories of the skin-friction coefficient, Nusselt number, and Sherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For the current problem, Boussinesq's approximation is applicable [39]. Thus, with all the above considerations, the relevant equations governing the supercritical couple stress convection boundary layer flow over the vertical cylinder [41,42,55] are given as follows:…”
Section: Model For Supercritical Heat Transfer From a Cylindermentioning
confidence: 99%
See 1 more Smart Citation
“…For the current problem, Boussinesq's approximation is applicable [39]. Thus, with all the above considerations, the relevant equations governing the supercritical couple stress convection boundary layer flow over the vertical cylinder [41,42,55] are given as follows:…”
Section: Model For Supercritical Heat Transfer From a Cylindermentioning
confidence: 99%
“…(12). The literature [55,69,70] provides a clear picture of these derivations and appropriate boundary conditions.…”
Section: Heat Flow Visualization In Supercritical Fluid Regionmentioning
confidence: 99%
“…They found that with an increase in the Lorentz force, the temperature profile improved. Rani et al 24 investigated the double‐diffusive boundary layer flow through the vertical cylinder. Raju et al 25 studied the effect of cross diffusions on the flow of the CS fluid through a porous tube, which is performed electrically.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, Rani and Reddy [28] studied the heat lines for couple stress thermal convection from a vertical cylinder. Later, couple stress thermosolutal convection along a vertical cylinder was scrutinized by Rani et al [29] using the concept of heat line and also mass line visualization. Using the same idea, recently Das and Basak [30] analysed the rate of heat transfer at different zones within enclosures involving discrete heaters.…”
Section: Introductionmentioning
confidence: 99%